Experimental Investigation of Ethene Decomposition by Video – Determination of Physical Data for Simulation Model. Issue 5 (12th March 2019) - Hilfer, Anton; Degenkolb, Jonas; Busch, Markus
Abstract: In this work, the decomposition reaction of ethylene is investigated in a high‐pressure view cell. Thus, for the first time, it is possible to precisely determine the velocity and structure of the flame front under high pressure. On one hand, the experiments should provide a better understanding of the decomposition process in a time and spatially resolved manner but also about the chemistry‐turbulence interaction. On the other hand, the experiments serve as a basis and validation for the development of a numerical simulation model. Abstract : The flame front propagation after a thermal decomposition of ethylene is investigated under high pressure. For this purpose, the experiments are performed in a view‐cell autoclave and recorded with a high‐speed camera. As a result, a correlation for the flame‐front speed can be defined as a function of pressure and temperature.